2008
DOI: 10.1016/j.jcp.2008.04.039
|View full text |Cite
|
Sign up to set email alerts
|

A new Savage–Hutter type model for submarine avalanches and generated tsunami

Abstract: In this paper we present a new two-layer model of Savage-Hutter type to study submarine avalanches. A layer composed of fluidized granular material is assumed to flow within an upper layer composed of an inviscid fluid (e. g. water). The model is derived in a system of local coordinates following a non-erodible bottom and takes into account its curvature. We prove that the model verifies an entropy inequality, preserves water at rest for a sediment layer and their solutions can be seen as particular solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 45 publications
5
141
0
Order By: Relevance
“…A similar approach can be found in the paper by Fernández-Nieto et al [6] for the description of a one-dimensional shallow flow of two immiscible layers.…”
Section: Shallow Flow Equationsmentioning
confidence: 76%
See 2 more Smart Citations
“…A similar approach can be found in the paper by Fernández-Nieto et al [6] for the description of a one-dimensional shallow flow of two immiscible layers.…”
Section: Shallow Flow Equationsmentioning
confidence: 76%
“…In Sect. 6 we show that, when a shallow over-saturated mixture, with water as the fluid constituent, is at rest on a slightly curved basal topography, the modeling equations predict a horizontal free surface. We end with conclusions in Sect.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…These four LGW types consist of several waves with respectively a symmetrical wave profile, a longer wave through than the wave crest, one dominant wave crest, and one dominant wave containing a large amount of air in the wave front (Heller and Hager 2011). They also hold the smallest to the largest amounts of mass transports, respectively (Di Risio et al 2011). The laboratory investigations of Kamphuis and Bowering (1970) on SALGWs showed that the LGW characteristics were mainly a function of the slide volume and the Froude number of the slide upon impact with the water.…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…Some models that analyse turbidity currents are available, and recently, a cellular automata model was also developed that is suitable for such a phenomenon (Salles et al, 2007). Only one numerical model that can simulate underwater granular flows (like rock and debris avalanches) with a Savage-Hutter type model (Fernández-Nieto et al, 2008) has been recently developed; nevertheless, this model has not been applied to real landslides yet.…”
Section: Introductionmentioning
confidence: 99%